ВИДЕОЛАПАРОСКОПИЧЕСКОЕ УШИВАНИЕ ПЕРФОРАТИВНЫХ ГАСТРОДУОДЕНАЛЬНЫХ ЯЗВ - Керимов, Мусабек Керимович; Коханенко, Николай Юрьевич; Луговой, Андрей Львович; Данилов, Сергей Александрович; Сериков, Валерий Александрович (Медицина: теория и практика, 2020)